Chlorine activated stacking fault removal mechanism in thin film CdTe solar cells: the missing piece - Peter Hatton (Nature Portfolio, 2021)
Stacking fault removal and improvement in CdTe solar efficiency is known to be correlated, yet the nature of the relationship is not well-established. Here, the authors explain the passivation process responsible for this improvement, and also elucidate the associated stacking fault removal mechanism.